Predicting Transfer of Generic Information Literacy Competencies by Non-Traditional Students to Their Study and Work Contexts: A Longitudinal Perspective - Laurent Testers; Aldin Alijagic; Saskia Brand-Gruwel; Andreas Gegenfurtner (MDPI AG, 2024)
Rapid developments in contemporary societies not only ask for lifelong learning but increasingly also for training in generic competencies suitable for multiple contexts and life stages. An indicator of training success is the transfer or application of new learning, a longitudinal process influenced by various theory- and evidence-based factors. The present study combined a multi-contextual and longitudinal approach by investigating non-traditional distance education students' intention to transfer newly acquired generic information literacy competencies to their study and work contexts before, directly after, and three months after training. Three surveys, using a combination of Ajzen's theory of planned behavior and Holton et al.'s Learning Transfer System Inventory model, measured the influence of performance outcomes expectations, organizational openness to change, and performance self-efficacy on intention to transfer and transfer behaviour. The participants were 82 adult educational professionals enrolled in an online information literacy course at the Open University. Partial least squares-based structural equation modelling (PLS-SEM) confirmed the value of employing a multi-contextual and longitudinal approach within this specific setting. Furthermore, notably, self-efficacy appeared to predict pre-training intention in both study and work contexts and transfer behaviour in the work context. Educational implications, limitations, and directions for future research are discussed.